Penerapan Metode Audio Lingual dalam Pembelajaran Maharah Al-Istima’ pada Santri Putra Panti Asuhan Anak Yatim Muhammadiyah Sukoharjo Tahun Ajaran 2021/2022 - Rahmat Hidayat (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2021)
The learning outcomes of the students are very important, as they reflect the level of success in the teaching and learning process. The problem in this study is how the learning process of Maharah al-Istima’ (listening skills) is conducted for the male students at the Muhammadiyah Orphanage in Sukoharjo, and how the Audio-Lingual method is implemented. The purpose of this research is to find out how the Audio-Lingual method is applied in the teaching process at the Muhammadiyah Orphanage in Sukoharjo and to understand how this method is used in teaching Maharah al-Istima’. This study uses an applied qualitative research method. The results of this research show that some students at the junior high school level (SMP) are not yet able to follow Arabic language lessons quickly, there is a lack of interest in Arabic language subjects, the sentences used are sometimes unfamiliar to the students, and the students’ vocabulary mastery in Arabic is still weak.